Avocado paste from industrial byproducts as an unconventional source of bioactive compounds: characterization, in vitro digestion and in silico interactions of its main phenolics with cholesterol - Zúñiga-Martínez, Shain; Abraham, Wall-Medrano; Dominguez-Avila, Jesus Abraham; Ayala-Zavala, J. Fernando; Hernandez-Paredes, Javier; Salazar-Lopez, Norma J.; Villegas-Ochoa, Monica A.; Gonzalez-Aguilar, Gustavo (2021)
Avocado cv. ‘Hass’ paste is the main byproduct derived from industrial avocado processing, and contains various bioactive compounds (BCs). Consumption of these compounds from different sources has been associated with positive health effects, although studies of avocado byproducts remain minimal. Avocado paste was analyzed, regarding its physicochemical properties, proximate composition, main BCs, antioxidant capacity, in vitro digestion and in silico interactions of its three main phenolics with cholesterol. Avocado paste contained 14.2% of lipids and 13.8% of protein. Total phenolic compounds were 2.1 mg GAE/g dw, with a phenolic profile that contained phenolic acids (ferulic, protocatechuic and p-coumaric acids) as its main compounds. Carotenoids (mainly β-carotene), tocopherols (mainly α-tocopherol), fatty acids (mainly oleic acid) and other BCs were also identified and quantified. Release of its phenolic compounds and antioxidant capacity were highest in the gastric phase of an in vitro digestion. In silico analyses showed that ferulic acid had the strongest interaction with cholesterol, suggesting a possible mechanism to inhibit its intestinal absorption. According to its composition and characteristics, it is possible to suggest avocado paste may be used as an unconventional source of BCs, with possible effects on cholesterol digestion.